An rbcL sequence from a Miocene Taxodium (bald cypress). - Soltis, P S (1992)
During the past decade, ancient DNAs from both animals and plants have been successfully extracted and analyzed. Recently, the age of DNA that can be recovered and sequenced was increased manyfold by the amplification and sequencing of a DNA fragment from a Magnolia fossil obtained from the Miocene Clarkia deposit (17-20 million yr old). However, the validity of this report has been questioned based on models predicting that DNA should be completely degraded after 4 million yr. We report here the successful amplification, sequencing, and analysis of a 1320-base-pair portion of the chloroplast gene rbcL from a Miocene Taxodium specimen, also from the Clarkia site. These data not only validate the earlier report of sequence data for a Magnolia species from the same site but also suggest that it may be possible to isolate and sequence DNAs routinely from the Clarkia deposit. The ability to recover and sequence DNAs of such age offers enormous research possibilities in the areas of molecular evolution, biogeography, and systematics.